Re-dating the Lower Pecos Canyonlands SMM (Skiles) mummy burial, dating a red-colored deerskin strap. (December 2021) - Rowe, Marvin W.; Blinman, Eric; Wacker, Lukas; Welte, Caroline
Highlights: Re-examination of prior 14 C date for colon contents of mummy SMM. Eight new 14 C dates on red deerskin strap disagree with the prior date. Red dye of deerskin strap is iron ocher, not cochineal or other organic pigment. Nondestructive 14 C analysis using plasma extraction is demonstrated. Prior 14 C date (TX-980) probably in error. Abstract: An early 1980s University of Texas (UT) radiocarbon ( 14 C) decay-based assay of colon contents from mummy SMM recovered from southwest Texas (41VV656) placed the death at 1150 ± 70 14 C years ago. This mummy of a "relatively tall, gracile adult male" was discussed in some detail in a comprehensive paper on Late Archaic mortuary practices in the Lower Pecos River region. The megacolon of the mummy was described as a condition that is usually associated with Chagas disease, caused by Trypanosoma cruzi . A red colored deerskin strap had encircled the mummy, restraining the distended colon, and a portion of the strap was submitted for additional radiocarbon dating to test the reliability of the original UT date. Using l ow e nergy p lasma r adiocarbon s ampling (LEPRS) at the Office of Archaeological Studies, Center for New Mexico Archaeology, we extracted CO2 by oxidation of organic material from four pieces of the strap and obtained eight 14 C dates at the ETH-Zürich MICADAS AMS facility. Multiple samples were prepared to deal with the possibility of contamination from lacquer/shellac/varnish that was probably applied during the 1930s and of contamination from decades of handing. Our best estimate of the age of that burial is an average of four dates on a piece of the strap where all surfaces had been physically removed to avoid potential surface contamination. This average is 780 ± 30 14 C years BP, 370 years more recent than the previous UT determination. It is likely that the original radiocarbon date is incorrect, and the difference is consistent with two other redatings of UT 14 C dated contexts where more recent assays have been roughly 400 years younger when compared to the UT laboratory dates.